Sliding Mode Controller for Trajectory Tracking Control of Autonomous Mobile Robot - Oon Thay, Ang; Mohd Basri, Mohd Ariffanan; Mohd Subha, Nurul Adilla; Shamsudin, Mohamad Amir; Sahlan, Shafishuhaza (ELEKTRIKA- Journal of Electrical Engineering, 2018)
Trajectory tracking control is an important issue in the field of autonomous mobile robot. In high speed and heavy load applications, the dynamic of autonomous mobile robot plays an important factor in allowing the robot to follow the desired trajectory path. However, the parameters attribute to robot dynamic are difficult to model and highly uncertain. One of the uncertainty factors is the load variation which changes the dynamic parameters of autonomous mobile robot. Meanwhile, Sliding Mode Control (SMC) is well known for its robustness against model uncertainties and disturbances. This paper is about design of dynamic controller based on SMC technique for trajectory tracking control of autonomous mobile robot system. The model of mobile robot is developed based on Pioneer 3-DX mobile robot. The trajectory tracking controller is divided into two parts, kinematic controller and dynamic controller. Stability of both dynamic and kinematic controller is verified using Lyapunov stability theory. The performance of trajectory tracking control for proposed dynamic controller based on SMC technique is compared against dynamic controller based on Proportional-Integral-Derivative (PID) technique with and without the presence of dynamic uncertainties. Simulation results show proposed dynamic controller based on SMC technique give better performance in trajectory tracking control in comparison to PID.